Iminosugars: promising therapeutics for influenza infection - Tyrrell, B; Sayce, A; Warfield, K; Miller, J; Zitzmann, N (Taylor and Francis, 2016)
Influenza virus causes three to five million severe respiratory infections per year in seasonal epidemics, and sporadic pandemics, three of which occurred in the 20th century and are a continuing global threat. Currently licensed antivirals exclusively target the viral neuraminidase or M2 ion channel, and emerging drug resistance necessitates the development of novel therapeutics. It is believed that a host-targeted strategy may combat the development of antiviral drug resistance. To this end, a class of molecules known as iminosugars, hydroxylated carbohydrate mimics with the endocyclic oxygen atom replaced by a nitrogen atom, are being investigated for their broad-spectrum antiviral potential. The influenza virus glycoproteins, haemagglutinin and neuraminidase, are susceptible to inhibition of endoplasmic reticulum α-glucosidases by certain iminosugars, leading to reduced virion production or infectivity, demonstrated by in vitro and in vivo studies. In some experiments, viral strain-specific effects are observed. Iminosugars may also inhibit other host and virus targets with antiviral consequences. While investigations of anti-influenza iminosugar activities have been conducted since the 1980s, recent successes of nojirimycin derivatives have re-invigorated investigation of the therapeutic potential of iminosugars as orally available, low cytotoxicity, effective anti-influenza drugs.